Editorial - Maya Sánchez, Mario (Boletín Geológico, 2021)
Boletín Geológico published issue 48(2) in December 2021, with the following articles (Figure 1): Velásquez et al. from Universidad Nacional de Colombia, Facultad de Minas, Medellín, present the Terciario Carbonífero de Antioquia (TCA), published by Dr. Jakob Emil Grosse in 1926, one of the most relevant classic works of Colombian geology in the first half of the XX century, in which its rigorous execution, excellent field control, and meticulousness in petrological and structural analyses stand out as one of the most valid and influential classic works, mainly for studies involving regional geology and economic geology. Oliveras, Colombian consultant, presents two analytical solutions to measuring the carbon dioxide (CO2) mass flux in a volcanic environment. CO2 mass flux must be measured continuously and telemetrically to obtain a better understanding of the dynamics of volcanic degassing processes, contributing to the creation of a volcano behavioral model. Gallego, from Servicio Geológico Colombiano, Bogotá, assesses the mineral demand in Colombia in the 2020-2050 period for the rare earth elements embedded in the deployment of wind power technologies in four different climate policy scenarios to establish whether they could face geological bottlenecks that could ultimately hamper the transition to a low-carbon economy. Rojas and Molina, from Universidad de los Andes, Bogotá, characterize a hydrocarbon reservoir of two fields in the Carbonera Formation within the Llanos Orientales Basin of Colombia. This was conducted using well logs, the structural surface of the regional datum of the area, segments of the Yuca Fault and a local fault in the reservoir, the permeability equation, and J functions of the reservoir provided by the operating company. Suarez et al., from Servicio Geológico Colombiano, Bogotá, propose a methodology for the recognition of extensional environments that integrates prefield photogeological interpretation, the establishment of a systematic process for data acquisition and structural analysis with a stereographic projection grid. Additionally, some basic concepts for the description and understanding of the structures and the mechanisms that generate them are included. Patarroyo, from Universidad Nacional de Colombia, Bogotá, presents data on the lithostratigraphy, nomenclature and biostratigraphy of the Yuruma Formation at its type locality, as well as nearby outcrops located to the north in Punta Espada, Guajira Department, Colombia. Aguiar and Serrano, from Universidad de las Fuerzas Armadas ESPE and Universidad Laica Eloy Alfaro, Ecuador, examine six models with strong motion equations. They determined the average spectra for soil profiles and proposed new spectral forms for the urban area of the city of Ambato. Boletín Geológico acknowledges the collaboration of the following reviewers and their commitment to the peer-review process involved in this issue: Agnes Mazot - GNS Science, New Zeland Alejandra Tironi - Universidad Nacional del Centro de la Provincia de Buenos Aires, Argentina Alejandro Beltrán - Universidad EAFIT, Colombia Andrés Cárdenas - Universidad EAFIT, Colombia Ángel Nieto Samaniego - Universidad Nacional Autónoma de México, México Angélica Triana – Universidad Externado de Colombia y Universidad de los Andes, Colombia Beatriz Aguirre - Universidad de Buenos Aires, Argentina Berenice Solis - Universidad Nacional Autónoma de México, México Camila Marques dos Santos - Centro de Desenvolvimento da Tecnologia Nuclear, Brazil Camilo Ordóñez - Universidade Federal do Rio de Janeiro, Brazil Carlos Guzmán - Universidad de Caldas, Colombia Carlos Mario Echeverri - Universidade Federal Campina Grande, Brazil César Mora - Cuencas Consultores, Colombia Diana Ortega - Universidad EAFIT, Colombia Fernanda Cravero - Centro de Tecnología de Recursos Minerales y Cerámica, Argentina Gabriel París – Consultant, Colombia Georgina Ibarra - Universidad Nacional Autónoma de México, México Gustavo Hincapié - Universidad de Caldas, Colombia Jorge López – LOGEA, Colombia Leandro Rodríguez - Centro Regional de Sismología para América del Sur (CERESIS), Perú Leda Sánchez Bettucci - Universidad de la República, Uruguay Marcelo Assumpção - Universidad de Sao Paulo, Brazil María Isabel Marín - Universidad EAFIT, Colombia Mariana Jácome - Universidad Nacional Autónoma de México, México Nelly Piragauta – Consultant, Colombia Verónica Vennari – IDEVEA (UTN-CONICET), Argentina